HUMAN RIGHTS OF THE FOURTH GENERATION IN A SINGLE EDUCATIONAL AREA - L. Kokhan, Hanna; I. Leonenko, Maksym; M. Perepolkin, Serhii; L. Syroid, Tetiana; V. Stryzhak, Iya (Revista Gênero e Interdisciplinaridade, 2020)
The relevance of the issue under study is determined by human rights appearance at the end of the XX the beginning of the XXI centuries that cannot be attributed to any of the three generations of human rights known to scholars; the doctrinal grounds of the necessity to unite them within the fourth generation of human rights; the lack of a universally recognized understanding of human rights of the fourth generation, and the ambiguous practice of their recognition and implementation on both the domestic and international levels.The purpose of the article is to develop the authors’ model of understanding the concept and classification of human rights of the fourth generation and to make suggestions aimed at getting more acquainted with them representatives of different peoples, to recognize them as quickly as possible and to ensure the most effective application in real life. The key method applied in the fourth generation of human rights research is generalization of the existing concepts of their interpretation within national law of different states, within international law, in the European Court of Human Rights practice, and in the doctrinal views of scientists. This title can be extended to rights not belonging to the first, the second and the third generations of human rights that have arisen at the end of the XX the beginning of the XXI centuries, as well as to human rights that will be revealed and interpreted in the future. As the fourth generation of human rights is in the process of its settling, the approaches to the classification of human rights based on exhaustive lists cannot fully reflect its real state. The content of this article may be of use to scholars studying human rights of the fourth generation, to lecturers teaching subjects dedicated to human rights, to students studying human rights, and to representatives of states and international organizations. involved in the development, recognition and practical implementation of human rights issues.